Risk Factor Profile of Chronic Energy Deficiency in First Trimester Pregnant Women in Primary Health Care Facilities - Friska Oktaviana; Evita Widyawati (CV. Global Health Science Group, 2025)
Chronic Energy Deficiency (CED) in pregnant women remains a major health concern due to its impact on the health of both the mother and her unborn baby. This condition is influenced by various factors, such as the mother's age, education level, and family economic situation. This study aims to identify factors contributing to the incidence of Chronic Energy Deficiency (CED) in pregnant women. This study used a quantitative descriptive approach and was conducted at the Kauman Community Health Center, Tulungagung Regency, from April to May 2025. The study sample included all pregnant women in their first and second trimesters who experienced CED and had received antenatal care (ANC). A total of 34 respondents were selected using a total sampling method. Data was collected through a closed questionnaire that had passed validity and reliability tests and was distributed online via Google Forms. The variables studied included maternal age, education level, and family income. Univariate analysis was performed to describe the frequency distribution and percentage of each variable. The study results show that the majority of pregnant women experiencing CED are in a relatively safe age range (74%), have a secondary education (53%), and come from families with low economic status (53%). These results indicate that CED is not only experienced by vulnerable age groups but is also influenced by educational and family economic factors. In conclusion, the incidence of CED in pregnant women is influenced by various interrelated factors, including factors of age, education and family income